Postnatal neuronal apoptosis in the cerebral cortex: physiological and pathophysiological mechanisms - Nikolić, Marina; Gardner, Humphrey; Tucker, Kerry (Neuroscience, 2013)
In the first week of postnatal life of all examined mammalian species, there is a wave of apoptosis in the cerebral cortex, accounting for a loss of up to 30% of neuronal content from birth to adulthood. In this review we examine recent advances in the understanding of this curious phenomenon. We survey the phenomenological literature and elaborate a putative relationship between the formation of active neuronal networks and selective apoptosis of non-participatory neurons. The underlying reason for this apoptotic wave remains unclear, but molecular mechanisms are starting to be elucidated that account for its mechanism, including a role for insulin-like growth factor I (IGF-1) and the Rho GTPases RhoA and RhoB. In addition, we discuss pathophysiological situations in which a variety of common drugs used either recreationally or for medical purposes, or pharmacological blockade of N-methyl-d-aspartate receptor (NMDAR) function, can also cause massive levels of apoptosis in this same developmental window. Experimentation linking molecular causes of developmental and pathophysiological apoptosis in postnatal cerebral cortex is discussed.
Gesehen am 25.11.2021